Analisis Perkembangan Klasifikasi Ilmu Dalam Pandangan Islam - Dewi, Trisia Megawati Kusuma; Pulungan, Muhammad Syukri (CENDEKIA, 2024)
The development of scientific classification occurred gradually along with the development of science both in the West and in the Islamic world. This article aims to explore ideas about the classification of science based on Western and Islamic perspectives. This research is qualitative research with a library research method based on author searches sourced from several relevant books and journals. The research results confirm that the development of science creates dichotomization and antagonism of various branches of science in the Western view. However, from an Islamic perspective, forms of knowledge and various branches of knowledge are one unit, even though the development of science in Islam was influenced by scientists from Greece. Some of the figures quoted in this article include Comte, Popper, Kuhn, and Habermas. Meanwhile, Muslim scientists come from the opinions of al-Farabi, Ibn Sina, Ibn Khaldun, and several other Muslim scientists. While in classical times there were only large classifications, currently there are special notations with special numbering to classify science in detail. The classification of Islamic sciences carried out by Muslim scientists emphasizes that the scope of knowledge in Islam is very broad, covering worldly and everyday affairs. The limitation of science is that the development of science must be within the framework of monotheism within the framework of devotion to Allah, and for the benefit of humanity. The classification of science in the Western view tends to be more secular and materialistic, while the Islamic view offers a more holistic view that integrates the physical and spiritual aspects. Both approaches provide valuable insights and can complement each other in the effort to achieve a fuller and deeper understanding of the world and our place in it.